Molecular Analysis of Synedrela Nodiflora (L.) Gaertn. Resistance Against Fomesafen using RAPD Markers - Murni Dwiati; Agus Hery Susanto (Fakultas Biologi | Universitas Jenderal Soedirman, 2015)
Both morphological and protein studies reveal that differences are observed between resistant Synedrella nodiflora against fomesafen and its susceptible wildtype. These are, however, more or less influenced by environmental factors, so that molecular analysis employing DNA markers is necessarily required. The methods involved total genomic DNA extraction using modified CTAB protocol following Doyle & Doyle (1990), RAPD marker amplification and visualization of RAPD markers prior to data analysis. Ten RAPD markers were used, but only seven of them showed polymorphism. Calculation of genetic distance and variation was carried out employing PopGen software.Based on the RAPD markers used in this study, it can be concluded that genetic distance between susceptible and resistant S. nodiflora is higher than that within susceptible samples supporting our previous morphological and protein data, although genetic variation among susceptible individuals seems to be significantly high.